Data on the diet and nutrition of urban and rural bumblebees - Joan Casanelles-Abella; Simonetta Selva; Alexander Keller; Fabian A. Ruedenauer; Bertrand Fournier; Sara D. Leonhardt; Marco Moretti (Scientific Data)
Abstract Land-use changes, driven by agricultural intensification and urbanization, are major contributors to biodiversity loss, altering habitats and reducing available resources. These changes impact species’ foraging strategies, particularly in human-modified ecosystems. While dietary shifts due to land-use changes have been well-studied in vertebrates, similar research in invertebrates, such as wild bees, remains limited. The present data paper provides a comprehensive dataset on the pollen collected from urban and rural populations of two bumblebee species (Bombus lapidarius and B. pascuorum) in Switzerland, examining pollen composition, nutrient content, and diet breadth. Additionally, by analyzing pollen from both body and leg-baskets, the dataset also offers a comprehensive overview of plant-bumblebee interactions. The data help understand plant-bumblebee interactions, pollination services, nutritional supply to larvae, and the impact of land-use changes on these processes. Furthermore, the dataset can be integrated with existing plant trait data to explore the effects of non-native species and other ecological factors on bumblebee foraging and nutrition in anthropogenically modified landscapes.